Bactericidal and antimicrobial effects of pure titanium and titanium alloy treated with short-term, low-energy UV irradiation. Issue 2 (February 2017) - Itabashi, T.; Narita, K.; Ono, A.; Wada, K.; Tanaka, T.; Kumagai, G.; Yamauchi, R.; Nakane, A.; Ishibashi, Y.
Abstract : Objectives: The surface of pure titanium (Ti) shows decreased histocompatibility over time; this phenomenon is known as biological ageing. UV irradiation enables the reversal of biological ageing through photofunctionalisation, a physicochemical alteration of the titanium surface. Ti implants are sterilised by UV irradiation in dental surgery. However, orthopaedic biomaterials are usually composed of the alloy Ti6Al4V, for which the antibacterial effects of UV irradiation are unconfirmed. Here we evaluated the bactericidal and antimicrobial effects of treating Ti and Ti6Al4V with UV irradiation of a lower and briefer dose than previously reported, for applications in implant surgery. Materials and Methods: Ti and Ti6Al4V disks were prepared. To evaluate the bactericidal effect of UV irradiation, Staphylococcus aureus 834 suspension was seeded onto the disks, which were then exposed to UV light for 15 minutes at a dose of 9 J/cm 2 . To evaluate the antimicrobial activity of UV irradiation, bacterial suspensions were seeded onto the disks 0, 0.5, one, six, 24 and 48 hours, and three and seven days after UV irradiation as described above. In both experiments, the bacteria were then harvested, cultured, and the number of colonies were counted. Results: No colonies were observed when UV irradiation was performed after the bacteria were added to the disks. When the bacteria were seeded after UV irradiation, the amount of surviving bacteria on the Ti and Ti6Al4V disks decreased at 0 hours and then gradually increased. However, the antimicrobial activity was maintained for seven days after UV irradiation. Conclusion: Antimicrobial activity was induced for seven days after UV irradiation on both types of disk. Irradiated Ti6Al4V and Ti had similar antimicrobial properties. Cite this article: T. Itabashi, K. Narita, A. Ono, K. Wada, T. Tanaka, G. Kumagai, R. Yamauchi, A. Nakane, Y. Ishibashi. Bactericidal and antimicrobial effects of pure titanium and titanium alloy treated with short-term, low-energy UV irradiation. Bone Joint Res 2017;6:108–112. DOI: 10.1302/2046-3758.62.2000619.